RANCANG BANGUN BEAMFORMING SENSOR PADA SISTEM AKUSTIK BAWAH AIR - Supartono, Supartono; Rusmana, Rusmana (Jurnal Teknologi Perikanan dan Kelautan, 2015)
Beamforming is the method used to create the radiation pattern of the antenna array by adding constructively the phases of the signals in the direction of the targets, and nulling the pattern of the interfing targets. Signal processing technique used is array sensors technology to create the transmission or reception of directional signal. Beamforming technique in underwater acoustics has been developed for a long time for the purposes of sonar, seismology, underwater communication, and identification of sound sources or submarines noise. If beamforming technique is used, so the signal strength, which is transmitted or percepted in a particular direction, will be much greater than the omnidirectional method or spherical sensors. Mastering the underwater technology is strategic, both simple technology and complex one, such as sonar or torpedo and the submarine. Countries mastering underwater technology will have the predominance in submarine warfare. Having a confidential nature and shocking system is a benefit of underwater weapon. Regarding to the mentioned problems, the study of beamforming sensor design was conducted with the expectations that the next generation of Indonesia can build the main instrument of defense system strength based on the strength of their own nation.